KEDUDUKAN ANAK PEREMPUAN DALAM MENERIMA HARTA WARISAN MENURUT HUKUM WARIS ADAT SUKU BIAK DI DAERAH PAPUA - NOVILDA ANASTASIA RUMWAROPEN (PREMISE LAW JURNAL, 2017)
ABSTRACT Biak tribe follows patrilineal kinship system which draws line of descent from father side (man). As what occurs in patrilineal system, in inheritance, the adat (customary) law of Biak tribe regulates that only the son who has the right to inherit his parents’ wealth which means that daughters have no right at all. The distribution of inheritance in Biak tribe occurs when a testator is still alive. Biak community follows individual ad collective inheritance system. Both son and daughter get inheritance although the share of the son is more than that of a daughter. When there is a dispute in the adat inheritance, the parties concerned choose the method of settlement by viewing the condition of the conflicting parties. Settlement can be done by negotiation in consanguinity by presenting ‘Mananwir’ or adat leaders or through Adat Biak Council, ‘Kankain Karkara Byak’. Keywords: Position of Daughter, Inheritance Law of Adat Biak Tribe